HIV DNA reservoir and elevated PD‐1 expression of CD4 T‐cell subsets particularly persist in the terminal ileum of HIV‐positive patients despite cART. Issue 5 (9th January 2021) - Horn, C; Augustin, M; Ercanoglu, MS; Heger, E; Knops, E; Bondet, V; Duffy, D; Chon, S‐H; Nierhoff, D; Oette, M; Schäfer, H; Vivaldi, C; et al.
Abstract : Objectives: Despite its importance as an HIV anatomic sanctuary, little is known about the characteristics of the HIV reservoir in the terminal ileum (TI). In blood, the immune checkpoint inhibitor programmed‐death‐1 (PD‐1) has been linked to the HIV reservoir and T‐cell immune dysfunction. We thus evaluated PD‐1 expression and cell‐associated HIV DNA in memory CD4 T‐cell subsets from TI, peripheral blood (PB) and rectum (RE) of untreated and treated HIV‐positive patients to identify associations between PD‐1 and HIV reservoir in other sites. Methods: Using mononuclear cells from PB, TI and RE of untreated HIV‐positive ( N = 6), treated ( n = 18) HIV‐positive and uninfected individuals ( n = 16), we identified and sorted distinct memory CD4 T‐cell subsets by flow cytometry, quantified their cell‐associated HIV DNA using quantitative PCR and assessed PD‐1 expression levels using geometric mean fluorescence intensity. Combined HIV‐1 RNA in situ hybridization and immunohistochemistry was performed on ileal biopsy sections. Results: Combined antiretroviral therapy (cART)‐treated patients with undetectable HIV RNA and significantly lower levels of HIV DNA in PB showed particularly high PD‐1 expression in PB and TI, and high HIV DNA levels in TI, irrespective of clinical characteristics. By contrast, in treatment‐naïve patients HIV DNA levels in memory CD4 T‐cell subsets were high in PB and TI. Conclusion: Elevated PD‐1 expression on memory CD4 T‐cells in PB and TI despite treatment points to continuous immune dysfunction and underlines the importance of evaluating immunotherapy in reversing HIV latency and T‐cell reconstitution. As HIV DNA particularly persists in TI despite cART, investigating samples from TI is crucial in understanding HIV immunopathogenesis.